2018
DOI: 10.1136/jech-2017-209984
|View full text |Cite
|
Sign up to set email alerts
|

Survival in relation to multimorbidity patterns in older adults in primary care in Barcelona, Spain (2010–2014): a longitudinal study based on electronic health records

Abstract: Mortality and survival vary according to CMPs in older adults stratified by sex and age. Our findings are useful for guiding the design and implementation of clinical management strategies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

11
14
1
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(27 citation statements)
references
References 28 publications
11
14
1
1
Order By: Relevance
“…As with the multimorbidity (3+) analysis, both males and females 80 years and older with multimorbidity (2+) were twice as likely to die as those without multimorbidity. Our results are consistent with those found in other studies 6 13 , 15 19 , 30 where the effect of multimorbidity on mortality decreased with age. Our results were consistent with Jani et al 12 that found that “Multimorbidity had a greater impact on all-cause mortality in middle-aged as opposed to older populations particularly males, which deserves exploration” (p. 1).…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…As with the multimorbidity (3+) analysis, both males and females 80 years and older with multimorbidity (2+) were twice as likely to die as those without multimorbidity. Our results are consistent with those found in other studies 6 13 , 15 19 , 30 where the effect of multimorbidity on mortality decreased with age. Our results were consistent with Jani et al 12 that found that “Multimorbidity had a greater impact on all-cause mortality in middle-aged as opposed to older populations particularly males, which deserves exploration” (p. 1).…”
Section: Discussionsupporting
confidence: 93%
“…Studies that included adults across age groups 6 12 generally found a higher effect of multimorbidity on mortality than those studies that included only older adults. 13 19 A few of these studies studied the relationship between multimorbidity and mortality and levels of deprivation and found higher deprivation was association with higher mortality, including lower education 6 , 20 and ethnicity. 8 …”
Section: Introductionmentioning
confidence: 99%
“…Studies on multimorbidity have increased in recent years,11–20 and a clinical guideline on clinical assessment and management of multimorbidity was developed by the National Institute for Health and Care Excellence in the UK in 2016 21. However, studies are still needed for the epidemiology and profiles of patients with multimorbidity and their longitudinal outcomes to inform policy-making in different populations including Chinese primary care patients 3 11.…”
Section: Introductionmentioning
confidence: 99%
“…However, studies are still needed for the epidemiology and profiles of patients with multimorbidity and their longitudinal outcomes to inform policy-making in different populations including Chinese primary care patients 3 11. Most studies on primary care patients with multimorbidity are conducted in western countries such as UK, USA, Australia, Spain and Belgium,14 15 22–28 and limited research has been conducted on psychological and social problems accompanying with multimorbidity 3 11 21 29 30. Several longitudinal studies of multimorbidity have been conducted in Asian populations,31–33 but none of these are of primary care patients.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation